G155(P) Outpatient paediatric cardiology services in a District General Hospital – impact of PEC clinics. (27th April 2016) - Venugopalan, P; Hristova, S; Abraham, D
Abstract : Aim: Presence of a designated Paediatrician with expertise in cardiology (PEC) at the District General Hospital (DGH) enables effective management of most of the cardiac referrals. The current study assessed the impact on outpatient cardiac services at a DGH since the appointment of a PEC. Methods: This was a retrospective study comparing outpatient cardiac services provided over two six month periods (January to June) in 2010 and 2014. In 2010, weekly outpatient clinics was run by a general paediatrician and a monthly joint cardiology clinic (JCC) was run with a tertiary cardiologist. In 2014, a local cardiac clinic run by PEC addressed the referrals while the tertiary cardiology clinics continued once a month (JCC). Data was collected from patients' records who attended both clinics in 2010 and 2014. Results: A total of 247 new cardiac referrals to the two clinics during both periods were analysed. The commonest indication for referral was heart murmur during both periods. The JCC had managed 89% of these referrals in 2010, while they were involved only in 2% of such referrals in 2014. Therefore the JCC was able to care for structural and post-operative heart disease children in 2014, whereas in 2010, majority of these children had to travel to the tertiary centre for their follow up. There was a decrease in healthy child referrals to the visiting paediatric cardiologist by 81%. It was also noted that direct GP referrals to the PEC clinic increased by 70% in 2014, confirming easy direct access to the PEC clinic for the primary care. However, waiting times did not improve. Conclusion: There has been significant improvement in cardiac patients followed up locally in the JCC, and direct access to specialist cardiac care at the DGH since the appointment of the PEC. There is a need for health economic evaluation to estimate the cost benefit of the PEC model for the NHS.